Pengetahuan Atlet Remaja Putri Papua Mengenai Female Athletes Triad (FAT): Gambaran Pengetahuan Atlet Remaja Putri Papua mengenai Female Athletes Triad (FAT) - Evi Sinaga; John Toding Padang; Daniel Womsiwor; Saharuddin Ita; Eva Sinaga (Universitas Airlangga, 2023)
Background: Female Athletes Triad (FAT) is a syndrome characterized by impaired energy availability, menstrual dysfunction, and low bone density. FAT might interfere with the health and performance of young female athletes in training and competition, which causes a decrease in achievement. Research on FAT is still limited in Indonesia, especially on indigenous Papuans. Objectives: To obtain a description of young Papuan female athletes' knowledge of FAT, including the three main components of FAT: danger, impacts, and risk factors for FAT. Methods: The total sample was 61 young female athletes with a convenience sampling technique. The survey method used a questionnaire consisting of questions related to athlete characteristics (age, ethnicity, training duration, and sports) and eight questions about FAT knowledge; it includes the three main components of FAT (osteoporosis, menstrual disorders, eating disorders), dangers and impacts, and the risk factors (age and physical activity). Results: Young Papua female athletes (80.33%) lacked knowledge about FAT. Most athletes (80.33%) had never heard of FAT. Most of the sample failed to identify FAT's three main components and risk factors correctly. Only five athletes (8.20%) correctly answered questions about fracture occurrence. Only six athletes (9.84%) could identify FAT components entirely and correctly, and about 11 (18.30%) answered correctly regarding the risk of excessive physical activity in athletes. Finally, only 23 athletes (37.70%) correctly answered questions about age. Conclusions: Young female Papuan athletes lack knowledge about the FAT components and risk factors.